PENGARUH EFISIENSI PEMESANAN, KEMUDAHAN PEMASARAN, DAN PENETAPAN HARGA PADA PENGGUNAAN E – KATALOG TERHADAP PERKEMBANGAN UMKM DI KABUPATEN MAGETAN - Samsu Anhari Faujianto; Ajid Indrayana; Ahadiati Rohmatiah; Mutmainah (Universitas Merdeka Madiun, 2023)
Micro, Small and Medium Enterprises (MSMEs) in Indonesia are one of the priorities in national economic development. MSMEs struggle to compete in a very dynamic business environment. Responding to competitive pressures, many MSME entrepreneurs use digital platforms to improve business strategies. One of the government programs developed is a procurement system based on an information system that contains lists, types of technical specifications, and prices of goods contained in a list called an electronic catalog.(e-catalogue).This study aims to determine the partial and simultaneous effect of ordering efficiency, ease of marketing and pricing on the use of e-catalogues on the development of MSMEs in Magetan Regency. The population in this study are e-catalogue providers and consumers in Magetan Regency. The sample in this study amounted to 30 providers e-catalogue. The method used in sampling is Non Probability Sampling selected is withSaturated Sampling .The research instrument used a questionnaire. Data analysis techniques used the classical assumption test, multiple linear regression analysis, analysis of the coefficient of determination, and hypothesis testing using the t test and F test with the help of the IBM SPSS 25 program. The results of this study indicated that partially and simultaneously ordering efficiency, ease of marketing and determination prices have a significant effect on the development of MSMEs in Magetan Regency.